PENGARUH MODEL PEMBELAJARAN TEAM QUIZ TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI KELAS XI IPS SMA NEGERI 2 SUNGAI PENUH - Iqbal Rahmat Putra; Khairani khairani (JURUSAN GEOGRAFI FIS UNP, 2023)
Abstract The purpose of this study was to determine whether there was an effect of the Team Quiz learning model on the learning outcomes of class XI IPS students at SMA Negeri 2 Sungai Penuh in the subject of geography. The type of research used was quasi-experimental. The population of this study were students of class XI IPS SMA Negeri 2 Sungai Penuh, totaling 124 students and the sample in this study used cluster random sampling technique with a sample of 60 students who were divided into experimental groups, namely class XI IPS 1 and control group class XI IPS 2 with the number of each group as many as 30 students. Data obtained from the results of tests given to students in the form of post-test questions given at the end of the learning process. The data analysis technique used is the normality test, homogeneity test, and hypothesis testing using the t-test formula. The results show that there is an effect of the Team Quiz learning model on student learning outcomes. (6.067 > 1.672) on the post-test results of the experimental class and the control class. This shows that there is an effect of the Team Quiz learning model on student learning outcomes in the geography subject of class XI IPS SMA Negeri 2 Sungai Penuh. Keywords : Influence, Team Quiz Learning Model, Learning Outcom